Integration of the Direct Instruction Teaching Model in Improving the Sport Massage Abilities of Physical Education Students - Rio Wakhid Hujjatul Islam; Muhammad Faisal Lutfi Amri; Muhamad Ilham (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Insufficient practical abilities, combined with theoretical readiness and minimal experience, mean that this scientific field does not get its share of the abilities of graduates and students. Describe the integration of the direct instruction teaching model on the results of sports massage abilities in the 2022 physical education study program students. Prove the effectiveness of the direct instruction teaching model on the results of sports massage abilities in the 2022 class of Physical Education and Physical Education study program students. The method used in this research is a quasi experiment, namely a systematic method that builds causal phenomena on others under controlled conditions. In testing the t test using a 2 tailed significance < 0.05, there is a significant influence between before being given the treatment and after being given the treatment. In the table above, a 2 tailed significance value of 0.00 is obtained, which means 0.00 < 0.005 p. This shows that there is a significant influence between before being given treatment and after being given treatment. For tcount = 49.637 while ttable = 1.980. Thus, it is known that tcount > ttable, namely 49.637 > 1.980, which means that there is a significant influence on the use of the direct instruction teaching model on the sports massage abilities of the 2022 physical education study program students.The direct instruction teaching model has 5 stages in an effort to improve students’ abilities, namely: Stage 1 conveying the objectives, Stage 2 Demonstrating, Stage 3 guiding the training, Stage 4 Checking understanding and providing assessment, Stage 5 Providing opportunities for application. There is a significant influence on the use of the direct instruction teaching model on the sports massage abilities of students in the 2022 physical education study program class.